Biomarkers of response to ocrelizumab in relapsing–remitting multiple sclerosis - Rodríguez-Jorge, Fernando; Fernández-Velasco, José Ignacio; Villarrubia, Noelia; Gracia-Gil, Julia; Fernández, Eva; Meca-Lallana, Virginia; Díaz-Pérez, Carolina; Sainz de la Maza, Susana; Pacheco, Eva María; Quiroga, Ana; Ramió-Torrentà, Lluis; Martínez-Yélamos, Sergio; et al. (Frontiers in Immunology, 2024)
Objective: To ascertain the changes of serum neurofilament light chain (sNfL) and glial fibrillary acidic protein (sGFAP) values in relapsing-remitting multiple sclerosis (RRMS) patients treated with ocrelizumab and their association with treatment response. Methods: Multicenter prospective study including 115 RRMS patients initiating ocrelizumab treatment between February/2020 and March/2022 followed during a year. Serum samples were collected at baseline and every 3 months to measure sNfL and sGFAP levels using single molecule array (SIMOA) technology. Based on age and body mass index, sNfL values were standardized using z-score. NEDA (Non-evidence of disease activity)-3 status was defined for patients free of disease activity after a year of follow-up. Inflammation (INFL) was considered when new relapses occurred during follow-up, or new MRI lesions were found at one-year exploration. PIRA (progression independent of relapse activity) was defined as disability progression occurring in absence of relapses or new MRI activity. Results: After a year on ocrelizumab, 85 patients (73.9%) achieved NEDA-3. Thirty patients did not achieve NEDA: 20 (17.4%) because of INFL and 10 (8.7%) because of PIRA. Of INFL patients: 6 (30.0%) had relapses, and 17 (85.0%) had at least one new MRI lesion on 12 months examination. At baseline, INFL patients had higher sNfL (p=0.0003) and sGFAP (p=0.03) than NEDA-3 group. PIRA patients mostly exhibited low sNfL and heterogeneous sGFAP levels. After a year, NEDA-3 and INFL patients showed similar decreases in sNfL (p<0.0001) and sGFAP (p<0.0001 for NEDA-3 and p=0.001 for INFL ones). However, the decrease occurred earlier in NEDA-3 patients. Accordingly, sNfL>1.5 z-score three months after ocrelizumab initiation indicated a higher risk of inflammation (OR=13.6; p<0.0001). Decrease of sGFAP values occurred later in both groups, with significant reductions observed at 12 months for INFL and 6 and 12 months for NEDA-3. No significant changes in sNfL or sGFAP were observed in PIRA patients. Conclusion: Ocrelizumab induced normalization of sNfL and sGFAP in the majority of NEDA-3 and inflammatory patients but did not cause changes in PIRA group. Our data suggest that normalization of sNfL and sGFAP associate with the lack of inflammatory-associated disease progression but it may not affect non-inflammatory PIRA.